2021
DOI: 10.33263/briac115.1368113694
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood Degree – Based Topological Indices of Graphene Structure

Abstract: The theory of chemical reaction networks is a branch of mathematics that aims to mimic real-world behavior. This research area has drawn many researchers' attention, primarily due to its biological and empirical chemistry applications. The fascinating problems that emerge from the mathematical structures involved have kindled the interest of pure mathematicians. In this paper, we estimate a few topological indices such as SK index, SK1 index, SK2 index, Modified Randić index, and Inverse Sum Index for the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Debasis Chanda et al [37] inspected applications of graph topology in the manufacturing of anti-cancer drugs and concentrated on the molecular structure of the anticancer medication manufacturing process utilised to make hyaluronic acidpaclitaxel conjugates in 2023. Vignesh et al [38] proposed some open neighbourhood indices, namely SK N , SK1 N , SK2 N , neighbourhood degree versions of Modified Randíc and Inverse sum indices in 2021 and studied the results based on the sum and products of the cardinality of edge partitions corresponding to four distinct Graphene structures. They are defined as follows:…”
Section: Fundamental Definitions and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Debasis Chanda et al [37] inspected applications of graph topology in the manufacturing of anti-cancer drugs and concentrated on the molecular structure of the anticancer medication manufacturing process utilised to make hyaluronic acidpaclitaxel conjugates in 2023. Vignesh et al [38] proposed some open neighbourhood indices, namely SK N , SK1 N , SK2 N , neighbourhood degree versions of Modified Randíc and Inverse sum indices in 2021 and studied the results based on the sum and products of the cardinality of edge partitions corresponding to four distinct Graphene structures. They are defined as follows:…”
Section: Fundamental Definitions and Literature Reviewmentioning
confidence: 99%
“…From table 15, it is observed that the calculated value of χ 2 for all the properties except MR, P and HAC are greater than the critical value of χ 2 obtained from the χ 2 distribution table at 5% level of significance with degrees of freedom 18. Thus, we accept only the models (32), (33) and (38).…”
Section: Linear Regression Modelsmentioning
confidence: 99%
“…Vignesh and Kalyani Desikan defined some neighbourhood degree sum based topological indices along with their reciprocal versions [13]. These indices are…”
Section: Introductionmentioning
confidence: 99%
“…Many such useful devices are associated with quantitative structure property relationship (QSPR), quantitative structure activity relationship (QSAR), and quantitative structure toxicity relationship (QSTR). These QSPR/QSAR/QSTR studies play a significant role in chemistry, mainly in drug design/ drug discovery [3][4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%